1979
DOI: 10.1111/j.1600-0714.1979.tb01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and ultrastructural relationship between oxytalan fibers in the periodontal ligament of the guinea pig

Abstract: The interfaces and the relationships between collagen and oxytalan fibers were observed d light and electron microscopy. Guinea pig periodontal ligament was prepared for light and electron microscopy with perfusion using Peter's buffered formalin for light microscopy and GTA‐S‐collidine and OSO4 for electron microscopic studies. The tissue for light microscopy was stained with a modified Gomori's aldehyde fuchsin technique, in which pre‐oxidization with potassium monopersulfate was carried out before staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The oxytalan fibers in the regenerated periodontal ligament had a light -and electron microscopical appearance similar to that in the normal periodontal ligament. The histological examination of the present material has also shown that the regenerated oxytalan fibers displayed a similar morphological appearance to those previously described by others in the normal animal and human periodontal ligament (Fullmer 1958, 1959, 1960, 1961, 1962, Fullmer et al 1974, Rannie 1963, Jonas & Riede 1980, Edwards 1968, Carmichael 1968, Hurst 1972, Sims 1973, 1975, 1977, 1979, Itoh et al 1979, Sampson & Sims 1979, Edmunds et al 1979, Sculean et al 1997).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The oxytalan fibers in the regenerated periodontal ligament had a light -and electron microscopical appearance similar to that in the normal periodontal ligament. The histological examination of the present material has also shown that the regenerated oxytalan fibers displayed a similar morphological appearance to those previously described by others in the normal animal and human periodontal ligament (Fullmer 1958, 1959, 1960, 1961, 1962, Fullmer et al 1974, Rannie 1963, Jonas & Riede 1980, Edwards 1968, Carmichael 1968, Hurst 1972, Sims 1973, 1975, 1977, 1979, Itoh et al 1979, Sampson & Sims 1979, Edmunds et al 1979, Sculean et al 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Oxytalan fibers have been described as being a normal component of the periodontal ligament connective tissue in man and various animal species (Fullmer 1958, 1959, 1960, 1961, 1962, Fullmer et al 1974, Goggins 1966, Rannie 1963, Lö e & Nuki 1964, Jonas & Riede 1980, Kohl & Zander 1962, Edwards 1968, Carmichael 1968, Sims 1973, 1975, 1977, 1979, Itoh et al 1979, Sampson & Sims 1979, Johnson & Pylypas 1992, Edmunds et al 1979, Sculean et al 1997. Usually, they are located closer to the cementum than to the alveolar bone, often inserting into the root cementum (Goggins 1966, Rannie 1963, Fullmer et al 1974, Carmichael 1968, Sims 1973, 1975, 1977, 1979, Itoh et al 1979, Sampson & Sims 1979, Sculean et al 1997.…”
mentioning
confidence: 99%
“…In previous examinations, oxytalan fibres were frequently arranged almost at right angles to the collagen fibres (Carmichael, 1968; Sims, 1973; Edmunds et al., 1979). However, this spatial relationship between oxytalan fibres and collagen fibre bundles is not consistent in the horse.…”
Section: Discussionmentioning
confidence: 76%
“…Oral research has contributed valuably to knowledge of the role of the fibroblast in the mechanisms of resorbing and forming collagen (Fullmer & Gibson 1966, Ten Cate 1972, Frank et al 1977. Subgroups of connective tissue fibers which are found in the lamina propria, e.g., elastin, reticulin, oxytalan , have been examined histochemically and ultrastructurally (Soames & Davies 1978, Edmunds et al 1979.…”
Section: The Basement Membrane Zone and Comments On The Subepithelialmentioning
confidence: 99%